Bacterial Volatiles (mVOC) Emitted by the Phytopathogen Erwinia amylovora Promote Arabidopsis thaliana Growth and Oxidative Stress - Ambra S. Parmagnani; Chidananda Nagamangala Kanchiswamy; Ivan A. Paponov; Simone Bossi; Mickael Malnoy; Massimo E. Maffei (MDPI AG, 2023)
Phytopathogens are well known for their devastating activity that causes worldwide significant crop losses. However, their exploitation for crop welfare is relatively unknown. Here, we show that the microbial volatile organic compound (mVOC) profile of the bacterial phytopathogen, Erwinia amylovora, enhances Arabidopsis thaliana shoot and root growth. GC-MS head-space analyses revealed the presence of typical microbial volatiles, including 1-nonanol and 1-dodecanol. E. amylovora mVOCs triggered early signaling events including plasma transmembrane potential Vm depolarization, cytosolic Ca2+ fluctuation, K+-gated channel activity, and reactive oxygen species (ROS) and nitric oxide (NO) burst from few minutes to 16 h upon exposure. These early events were followed by the modulation of the expression of genes involved in plant growth and defense responses and responsive to phytohormones, including abscisic acid, gibberellin, and auxin (including the efflux carriers PIN1 and PIN3). When tested, synthetic 1-nonanol and 1-dodecanol induced root growth and modulated genes coding for ROS. Our results show that E. amylovora mVOCs affect A. thaliana growth through a cascade of early and late signaling events that involve phytohormones and ROS.